2007
DOI: 10.1364/ol.32.003522
|View full text |Cite
|
Sign up to set email alerts
|

Tissue refractometry using Hilbert phase microscopy

Abstract: We present, for the first time to our knowledge, quantitative phase images associated with unstained 5 μm thick tissue slices of mouse brain, spleen, and liver. The refractive properties of the tissue are retrieved in terms of the average refractive index and its spatial variation. We find that the average refractive index varies significantly with tissue type, such that the brain is characterized by the lowest value and the liver by the highest. The spatial power spectra of the phase images reveal power law b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 18 publications
3
56
0
Order By: Relevance
“…In addition, the second phase peak in Fig. 6 (d) has a symmetrical shape which matches the previous literature [25]. …”
Section: Resultssupporting
confidence: 89%
“…In addition, the second phase peak in Fig. 6 (d) has a symmetrical shape which matches the previous literature [25]. …”
Section: Resultssupporting
confidence: 89%
“…Topography and its dynamics have been widely addressed, including imaging of human tissues and studying pathophysiology of live biological cells [41][42][43][44]. Holographic imaging techniques measure the optical light field Ex; y; λ Ax; y; λ· exp−iΔϕx; y; λ, consisting of amplitude Ax; y; λ and phase delay maps Δϕx; y; λ, which is diffracted by samples at a specific wavelength of light λ.…”
Section: B Holographic Imagingmentioning
confidence: 99%
“…[30][31][32] It has been shown that the knowledge of the amplitude and phase associated with an optical field transmitted through tissues captures the entire information regarding light-tissue interaction, including scattering properties. [33][34][35][36] Yet, the potential of QPI for label-free pathology has not been explored. Here we employ spatial light interference microscopy (SLIM), [37][38][39] a new white light QPI method developed in our laboratory, to image the entire unstained prostate and breast biopsies and perform a side-by-side comparison with stained pathological slides.…”
Section: Introductionmentioning
confidence: 99%